"Fundamentals of Engineering Thermodynamics (Formerly, Thermodynamics and Heat Engines, Vol.1) (SI Units)" - Yadav (R); Sanjay; Rajay ("18-C, Sarojoni Naidu MargAllahabad", 2004)
Thermodynamics
Keywords: Thermodynamics